2009
DOI: 10.1111/j.1365-2524.2008.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Out of Hospital’: a scoping study of services for carers of people being discharged from hospital

Abstract: Successive government policies have highlighted the need to inform and involve carers fully in the hospital discharge process. However, some research suggests that many carers feel insufficiently involved and unsupported in this process. This paper summarises a scoping review to identify what the UK literature tells us about the service provision for carers, and its effectiveness, around the time of hospital discharge of the care recipient, and also describes a mapping exercise of the work currently being done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…Previous research has shown that care transitions – such as between the home and hospital – can be a time where poor management occurs and there is an increased risk of medical complications (Borthwick et al . , Brock et al . , Cadogan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that care transitions – such as between the home and hospital – can be a time where poor management occurs and there is an increased risk of medical complications (Borthwick et al . , Brock et al . , Cadogan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Gaps in the provision of post-discharge care have been known to present a problem for health care delivery for some time, not only in Canada but elsewhere as well (Arbaje et al, 2008 ;Borthwick et al, 2009 ;Boughton & Halliday, 2009 ). The lack of effective transitional care after hospitalization has been linked to readmissions, especially among those with lower socioeconomic status and lack of social support (Arbaje et al, 2008 ).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Shortened hospital stays have become a hallmark of many health care systems. In this context, the lack of continuity of care during the transition from hospital to community has been identified as a problem with serious negative implications for the well-being of individuals in many countries where this has been studied, including Canada, the United States, the United Kingdom, Australia, Sweden, and Japan (Borthwick, Newbronner, & Stuttard, 2009 ;Boughton & Halliday, 2009 ;Efraimsson, Sandman, Hydén, & Rasmussen, 2006 ;Naylor, 2012 ;Tomura, Yamamoto-Mitani, Nagata, Murashima, & Suzuki, 2011 ).…”
mentioning
confidence: 99%
“…There has been a lack of research into interventions to support carers at hospital discharge in general: a scoping review of service provision for carers around hospital discharge found only five studies involved an intervention, none of which focussed on the discharge process as directly related to carers. 22 A systematic review of randomised controlled trials (RCTs) of discharge planning interventions found only 14 separate studies conducted over a 19-year period. 26 The review concluded that integration of caregivers into discharge planning reduces risk of hospital readmission, but was unable to determine the most effective method of caregiver integration.…”
Section: Introductionmentioning
confidence: 99%